2003
DOI: 10.1097/01.wcb.0000090680.07515.c8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Infiltration Increases Matrix Metalloproteinase-9 in the Ischemic Brain after Occlusion/Reperfusion of the Middle Cerebral Artery in Rats

Abstract: Summary:Matrix metalloproteinase-9 (MMP-9) activity increases in the brain during the first day after focal ischemia and might be involved in the pathogenesis of tissue damage. We previously showed MMP-9 in the extracellular space of brain parenchyma along with neutrophil recruitment after ischemia. In the present study, we tested whether neutrophils were a direct source of enhanced MMP-9 in the ischemic brain. Neutrophil infiltration was prevented either by injecting an antibody against ICAM-1, which abrogate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
191
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(199 citation statements)
references
References 37 publications
8
191
0
Order By: Relevance
“…In this early phase, in vivo and in vitro evidence is consistent with the paradigm that the endothelium promotes inflammation and recruits circulating leukocytes through the upregulation of adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1, E-selectin, and P-selectin (del Zoppo and Mabuchi, 2003). These recruited leukocytes then release metalloproteinases, which participate in the breakdown of the neurovascular matrix with consequent blood-brain barrier disruption, edema, and/or hemorrhage (Justicia et al, 2003;Kolev et al, 2003;Maier et al, 2004;Ponnampalam and Mayberg, 2004;Veldhuis et al, 2003;Wang and Lo, 2003). The importance of the inflammatory response in the pathophysiology of ischemic stroke is generally recognized.…”
Section: Introductionsupporting
confidence: 71%
“…In this early phase, in vivo and in vitro evidence is consistent with the paradigm that the endothelium promotes inflammation and recruits circulating leukocytes through the upregulation of adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1, E-selectin, and P-selectin (del Zoppo and Mabuchi, 2003). These recruited leukocytes then release metalloproteinases, which participate in the breakdown of the neurovascular matrix with consequent blood-brain barrier disruption, edema, and/or hemorrhage (Justicia et al, 2003;Kolev et al, 2003;Maier et al, 2004;Ponnampalam and Mayberg, 2004;Veldhuis et al, 2003;Wang and Lo, 2003). The importance of the inflammatory response in the pathophysiology of ischemic stroke is generally recognized.…”
Section: Introductionsupporting
confidence: 71%
“…It is widely accepted that in CNS disease, the increased MMP‐9 primarily come from infiltrating neutrophils 15, 16, 17. Removing neutrophils from the circulation prior to SCI with an anti‐neutrophil serum significantly reduces MMP‐9 level, which indicates that the increase in MMP‐9 after SCI come from neutrophils 17.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the treatment effect of GM6001 was paralleled by significantly reduced TBRs. Pharmacological intervention of MMPs leads to a marked reduction in lesion size, which might also affect downstream pathophysiological processes that are only indirectly related to MMP activity (Asahi et al, 2000;Rivera et al, 2002;Justicia et al, 2003;Magnoni et al, 2004). Such downstream effects may alter the compartmental distribution of intravenously injected compounds, which complicates the use of genetic or pharmacological manipulation of MMPs as control for the specificity of imaging approaches (Klohs et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%